Proceedings of the Creative Construction Conference 2019 2019
DOI: 10.3311/ccc2019-115
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Level Of BIM Implementation at South African Architecture Schools: A Qualitative Study

Abstract: It is a well-known fact the architecture industry is at the forefront of implementing and using Building Information Modelling (BIM) to conceptualize, develop, resolve and execute buildings. Although it may seem like a new concept, BIM had its foundations set in the 1980's with the disruption being 3D CAD. BIM has significantly been revolutionized beyond the likes of 3D CAD to become a complex system of information. Currently, BIM is still revolutionizing how architects design buildings by intelligently docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Disability-compliant lecture halls have high-quality audio and enhancement equipment to benefit students with hearing impairments. The seating arrangements in specific lecture halls restrict the participation and movement of individuals with physical impairments (Pillay and Gumbo, 2019). It has also been indicated that several university buildings allow for easy access inside the buildings but are restricted to certain areas such as offices, toilet facilities and other common areas, therefore not fully compliant with disability access.…”
Section: Causes Of Non-compliancementioning
confidence: 99%
See 2 more Smart Citations
“…Disability-compliant lecture halls have high-quality audio and enhancement equipment to benefit students with hearing impairments. The seating arrangements in specific lecture halls restrict the participation and movement of individuals with physical impairments (Pillay and Gumbo, 2019). It has also been indicated that several university buildings allow for easy access inside the buildings but are restricted to certain areas such as offices, toilet facilities and other common areas, therefore not fully compliant with disability access.…”
Section: Causes Of Non-compliancementioning
confidence: 99%
“…Students indicated dissatisfaction with toilet facilities in several buildings, such as narrow spaces inaccessible for wheelchair users, no adequate railing inside toilet spaces, and lack of braille signage for blind individuals to differentiate gender (Drafor and Jones, 2008). Facilities such as football fields and places of worship consist of vertically raked and slanting seating, making it difficult for individuals with physical impairments to access top seats (Pillay and Gumbo, 2019). Transport stations on campuses were the least disability-compliant facilities.…”
Section: Causes Of Non-compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Esta iniciativa de inserir uma unidade de BIM no currículo do Mestrado Integrado em Arquitetura, em continuidade com outras unidades que abordam o desenho digital e de modelação geométrica 3D, tem em vista atingir em alguns anos um ensino totalmente integrado no currículo da escola, à semelhança de outras universidades europeias que tiverem um hiato de cerca de 7 anos entre a introdução da primeira Unidade dedicada e o ensino de BIM de forma totalmente integrada [3], [4].…”
Section: Introductionunclassified